Outage probability due to intercore crosstalk in dual-core fiber links with direct-detection - Rebola, J.; Cartaxo, A.; Alves, T. M. F.; Marques, A. S. (IEEE Photonics Technology Letters, 2019)
The outage probability (OP) in short-haul direct-detection (DD) optical links supported by weakly-coupled multicore fiber (MCF) impaired by intercore crosstalk (ICXT) and using on-off keying signaling is assessed theoretically and through simulation. A closed-form expression for the OP is proposed for a single interfering core and validated for a 10 Gbit/s MCF link with 20 km and skew below 1 ps/km. This expression is useful to provide fast and reliable performance estimates in preliminary studies of weakly-coupled MCF-based systems where the ICXT is highly correlated along the signal bandwidth, i. e., for skew-bit rate products below 0.2. For high skew-bit rate products, i. e., when the ICXT is decorrelated along the signal bandwidth, simulation results show that, for a typical OP of 104, the tolerance to ICXT increases above 4 dB, when compared with low skew-bit rate products. It is also shown that DD links with finite extinction ratio are more robust to outage induced by the ICXT than those with ideal extinction ratio.